The Czechoslovak Librarianship 1945-1959 - Brozovska Onderkova, Jana (Folia Toruniensia, 2022)
The article focuses on the transformation of the role of public libraries in Czechoslovakia in the 1950s in dependence on the political development of the country. It describes the changes of educational goals of Czechoslovak librarianship in the reporting period and methods used in educational activities. In the period after the end of WWII, Czechoslovak librarianship continued its development, especially in the legislative area, on the foundations built during the 1918–1938 period. Even in the post-war period, the General Public Libraries Act remained in force and there was a coordination center for educational activities which after the end of the war adopted its original name - Masaryk Institute of Adult Education. However, after 1945, training and public librarianship were in a completely different social and political situation. The field of adult education and the public librarianship remained priority areas of interest for political representation and individual political parties that operated in post-war Czechoslovakia. The political representation of post-war Czechoslovakia cooperated intensively with the USSR, and the left-wing ideas had very strong position in the political and public life of the state. In the first part of the article, we study the efforts of the communists in the period 1945–1948 to control the public libraries, which were one of the most important elements of the educational system and were of importance, especially in the rural environment. The second part of the article focuses on the period 1948–1959. It shows the development in the field of legislation and on the examples of the activities of public libraries, it shows how they concentrated on their main task, i.e., how they worked with the reader.